Centralization efforts in the transformation of the Hungarian local government system - Badó, Attila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Following a change of government in 2010, the Hungarian local government system underwent a period of significant transformation. The question of how it is viewed and the effects it may have are currently being debated. However, the fact that 2011 saw a reform of a more than a 20-year-old unyielding system seems difficult to argue with. Laced with the democratic ideal of self-government, the Hungarian regime change of 1989 resulted in a  fragmented local government system with a considerable degree of management authority. The local government model opted for by Hungary, which can indeed be dubbed as the champion of decentralisation, could function uninterruptedly until 2010 with minor adjustments.The centralising effort of the government had already become clear beyond a  shadow of a  doubt before the adoption of the Cardinal Act or the Fundamental Law (2011) itself. The reorganisation of territorial public administration was the first series of measures which allowed to make inferences about the public administration system and the forthcoming centralisation of local governments.
Keywords: reform, local government, functional decentralization, centralization effort, debt settlement, increase of efficiency